2022
DOI: 10.3390/genes13081375
|View full text |Cite
|
Sign up to set email alerts
|

miR-23b-3p Modulating Cytoprotective Autophagy and Glutamine Addiction in Sorafenib Resistant HepG2, a Hepatocellular Carcinoma Cell Line

Abstract: Background: Hepatocellular carcinoma (HCC) is the second most common malignancy with increasing cancer deaths worldwide. HCC is mainly diagnosed at its advanced stage, and treatment with FDA-approved sorafenib, the multikinase inhibitor drug, is advised. Acquired resistance against sorafenib develops through several pathways involving hypoxia, autophagy, high glycolysis, or glutaminolysis. Small non-coding RNAs, similar to microRNAs (miRNAs), are also known to affect sorafenib resistance in HCC. However, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Beclin-1 KU-0063794 Silencing of Beclin-1 suppresses autophagy and increases drug sensitivity [243] CD13/p38/Hsp27/CREB/ATG7 5-flourouracil CD13 increases ATG7 expression via the p38/Hsp27/CREB axis, which induces chemoresistance [244] miR-23b-3p/ATG12 Sorafenib miR-23b-3p reduces ATG12 expression, impairing autophagy and reversing sorafenib resistance [245] p57/autophagy EGFR inhibitors p57 induces autophagy and enhances the potential of EGFR inhibitors in combating HCC [246] VRK2 JNK1/MAPK8/Bcl-2/Beclin-1 VRK2 induces Beclin-1 expression via activation of the JNK1/MAPK8 axis to mediate dissociation of Bcl-2 from Beclin-1, triggering autophagy and mediating drug resistance [247] Akt Sorafenib Suppression of Akt signaling reverses autophagy that promotes survival to autophagy that promotes death, thereby reversing drug resistance [248] miR-101-3p/Beclin-1 oxaliplatin miR-101-3p reduces the expression of Beclin-1 in inhibiting autophagy and reversing drug resistance [249] miR-651-3p/ATG3 Cisplatin miR-651-3p reduces ATG3 expression in suppressing autophagy and chemoresistance increase the formation of ROS and mediates oxidative stress [187]. Thus, when the levels of ROS decrease, the sensitivity of HCC cells to radiotherapy decreases.…”
Section: Targeting Autophagy For Regulating Radioresistancementioning
confidence: 99%
“…Beclin-1 KU-0063794 Silencing of Beclin-1 suppresses autophagy and increases drug sensitivity [243] CD13/p38/Hsp27/CREB/ATG7 5-flourouracil CD13 increases ATG7 expression via the p38/Hsp27/CREB axis, which induces chemoresistance [244] miR-23b-3p/ATG12 Sorafenib miR-23b-3p reduces ATG12 expression, impairing autophagy and reversing sorafenib resistance [245] p57/autophagy EGFR inhibitors p57 induces autophagy and enhances the potential of EGFR inhibitors in combating HCC [246] VRK2 JNK1/MAPK8/Bcl-2/Beclin-1 VRK2 induces Beclin-1 expression via activation of the JNK1/MAPK8 axis to mediate dissociation of Bcl-2 from Beclin-1, triggering autophagy and mediating drug resistance [247] Akt Sorafenib Suppression of Akt signaling reverses autophagy that promotes survival to autophagy that promotes death, thereby reversing drug resistance [248] miR-101-3p/Beclin-1 oxaliplatin miR-101-3p reduces the expression of Beclin-1 in inhibiting autophagy and reversing drug resistance [249] miR-651-3p/ATG3 Cisplatin miR-651-3p reduces ATG3 expression in suppressing autophagy and chemoresistance increase the formation of ROS and mediates oxidative stress [187]. Thus, when the levels of ROS decrease, the sensitivity of HCC cells to radiotherapy decreases.…”
Section: Targeting Autophagy For Regulating Radioresistancementioning
confidence: 99%
“…Similarly, it is also demonstrated that miR-23b-3p modulates the autophagy-induced drug resistance of sorafenib in the HCC HepG2 cell line, while it not only targets ATG12 but also GLS1 (glutaminase), which is related to the high exogenous glutamine that is associated with progressed disease [ 171 ].…”
Section: The Interplay Between Mirnas and Autophagy In Hccmentioning
confidence: 99%
“…Therefore, we conclude that miRNAs in HCC inhibit cellular autophagy and reverse HCC chemoresistance by altering the expression of autophagy-related genes or affecting key links in the autophagic process, providing new therapeutic targets for HCC. In Figure 4, we illustrate the mechanism by which some miRNAs enhance the chemosensitivity of HCC by mediating HCC cellular autophagy (91,96,(98)(99)(100).…”
Section: Regulated Cell Death 41 Autophagymentioning
confidence: 99%